Container creation scheduling method and device, medium and electronic equipment - BAO YONGCHENG; XU XINKUN; WANG SIWU; LIU HAIFENG (2020)
The embodiment of the invention provides a container creation scheduling method and device, a computer readable medium and electronic equipment. The container creation scheduling method comprises thesteps of obtaining information of a target mirror image layer of a to-be-created container in a cluster; determining statistical information of each node in the cluster about the target mirror image layer according to the information of the target mirror image layer; and determining a target node according to the statistical information of each node in the cluster about the target mirror image layer, wherein the target node is used for creating the to-be-created container. According to the technical scheme of the embodiment of the invention, the scheduling accuracy and the reasonable utilization of cluster resources are improved. 本发明实施例提供了一种容器创建的调度方法、容器创建的调度装置、计算机可读介质及电子设备，该容器创建的调度方法包括：获取集群中待创建容器的目标镜像层的信息；根据所述目标镜像层的信息确定所述集群中各个节点关于所述目标镜像层的统计信息；根据所述集群中各个节点关于所述目标镜像层的统计信息确定目标节点，所述目标节点用于创建所述待创建容器。本发明实施例的技术方案有利于提高调度准确性以